Transcription factor TCF4: structure, function, and associated diseases - R. R. Savchenko; N. A. Skryabin (Вавиловский журнал генетики и селекции, 2024)
Our understanding of human genes - particularly their structure, functions, and regulatory mechanisms - is still limited. The biological role of approximately 20 % of human proteins has not been established yet, and the molecular functions of the known part of the proteome remain poorly understood. This hinders progress in basic and applied biological and medical sciences, especially in treating hereditary diseases, which are caused by mutations and polymorphic variants in individual genes. Therefore, it is crucial to comprehend the mechanisms of protein functioning to address this problem. This further emphasizes the importance of investigating gene functions and molecular pathogenetic pathways associated with single-gene inherited diseases. This review focuses on the TCF4 gene that encodes a transcription factor crucial for nervous system development and functioning. Pathogenic variants in this gene have been linked to a rare genetic disorder, Pitt–Hopkins syndrome, and TCF4 polymorphic variants are associated with several socially significant diseases, including various psychiatric disorders. The pathogenetic mechanisms of these conditions remain unexplored, and the knowledge about TCF4 upregulation and its target genes is limited. TCF4 can be expressed in various isoforms due to the complex structure and regulation of its gene, which complicates the investigation of the protein’s functions. Here, we consider the structure and functions of the TCF4 transcription factor. We discuss its potential target genes and the possible loss-of-function pathogenetic mechanisms identified in animal and cellular models of Pitt–Hopkins syndrome. The review also examines the advantages and limitations of potential therapies for Pitt–Hopkins syndrome that are based on TCF4 dosage compensation or altering the activity of TCF4 target genes.